1959
DOI: 10.1172/jci103940
|View full text |Cite
|
Sign up to set email alerts
|

Urea Metabolism in Man*

Abstract: Urea has long been considered to be metabolically inert. However, recent studies with isotopic urea in several species of animals have revealed that urea is hydrolyzed in the alimentary tract even when administered parenterally (1-5). This breakdown is presumably due to the action of bacterial urease, since urea metabolism can be eliminated or reduced to negligible proportions by the administration of antibiotics.In the studies reported herein, labeled urea was administered intravenously to normal subjects and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
136
3

Year Published

1960
1960
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(145 citation statements)
references
References 15 publications
6
136
3
Order By: Relevance
“…Tracer studies indicate that at least 25 % of the urea in the body undergoes hydrolysis within the gut (Walser and Bodenlos, 1959), but a proportion of the ammonia produced is absorbed and re-synthesized to urea in the liver. The practical importance of this metabolic cycle, therefore, lies in the concentration of ammonia within the gut and its effect on the pH of the gastric and intestinal fluids.…”
mentioning
confidence: 99%
“…Tracer studies indicate that at least 25 % of the urea in the body undergoes hydrolysis within the gut (Walser and Bodenlos, 1959), but a proportion of the ammonia produced is absorbed and re-synthesized to urea in the liver. The practical importance of this metabolic cycle, therefore, lies in the concentration of ammonia within the gut and its effect on the pH of the gastric and intestinal fluids.…”
mentioning
confidence: 99%
“…Fasting adults seem to transport some 4-8 g ( 220-440 mmol) ammonia per 24h via the portal vein to the liver (28,29). Our group has documented enteric release of ammonium ions in piglets (33) of the same magnitude.Out of the endogenous urea production 1530% is hydrolyzed in the gut implying that this amount of ammonium ions (or urea) is recirculating as the faecal content is only 50 mg/24h (29).…”
Section: Bicarbonate Eliminationmentioning
confidence: 87%
“…Their calculations of the bicarbonate balance have confirmed that oxidation of many amino acids should in fact generate bicarbonate, but in addition Jungas et a1 (14) have found that the large production of acid (protons) in the urea cycle is balanced within the liver by a local amino acid oxidation generating large amounts of bicarbonate. Furthermore, it now seems to be proven that the same ammonium ion is recirculated and reused for the donation of protons to bicarbonate via an enterohepatic recirculation (16,28,29,30,31,32).…”
Section: Bicarbonate Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…A portion of urea production is not excreted, but is secreted into the colon, hydrolysed by the resident microflora and the resulting nitrogen containing compounds are salvaged and reutilized in the body (Walser and Bodenlos, 1959). Data by Danielsen and Jackson (1992) have indicated that the ability to maintain urea production is the primary driver of the salvage mechanism.…”
Section: Introductionmentioning
confidence: 99%